FEATURES OF COST AND MANAGEMENT ACCOUNTING IN CONSTRUCTION COMPANY - O. Ageeva; E. Kozhinova (Вестник университета)
The article is devoted to research features of methodical approaches of cost and management accounting in construction. The article describes the main characteristics of the classification of costs depending on the goals of the management accounting, summarizes the advantages and disadvantages most frequently used methods. Also it has been identified application features of methods of cost and management accounting based on the specifics of the construction industry.